Visibilidad, necesidad actual de nuestros docentes e investigadores: Visibility, current need of our teachers and researchers - Martín Herrera, María Luisa (Horizonte Pedagógico, 2020)
La divulgación de los resultados de las investigaciones constituye una etapa crucial en la que se socializan los avances científicos de los educadores, para ello hoy se necesita la rápida divulgación y evaluación a través de las redes sociales. En el presente trabajo, se hace un análisis a partir de las dificultades presentadas por nuestros docentes e investigadores de la visibilidad de sus artículos científicos fruto del trabajo de años de estudio, les brindamos algunas posibilidades con que contamos para estar actualizados y recurrir a fuentes de información en tiempo real, con los investigadores de las ciencias sociales e intercambiar con otros especialistas a través de la visibilidad de nuestras contribuciones. La importancia teórico-práctica está dada en que nuestros docentes e investigadores cuentan con orientaciones breves y precisas para divulgar y socializar sus artículos científicos en nuestras redes sociales: facebook, youTube, instagram, twitter whatsApp y otros, saber la influencia de nuestras investigaciones en otros estudiosos, que opinen y utilicen nuestros artículos como fuentes de información tienen que formar parte de los criterios evaluativos del docente o investigador en el futuro no muy lejano. Abstract: The process of inclusion of students with special educational needs constitutes, without a doubt, one of the most studied, debated and followed topics since the end of the last century to the present day by pedagogues and other specialists responsible for its materialization, both in Cuba and in the world. This article was focused to attention about one of the most controversial aspects of this phenomenon, the inclusion of deaf students in regular education, its conditioning factors, its concretion in practice, its results and consequences in the process of education and integral development of their personality . It was based on pedagogical experiences derived from exchange in school and extracurricular contexts with deaf children, adolescents, youth and adults, objects of this process. Scientific methods such as interview, survey and observation are used; as well as, the referential and the experiential. It had the objective of reflecting on determining aspects in the success of the socio-educational inclusion process of deaf students, based on the factors, conditions, conceptions and positions that are adopted regarding it. It is considered significant to offer a series of evidential arguments, based on the scientific theory and professional practice of the authors, from the research projects that are undertaken at the National Center for Overcoming and Development of the Deaf Person, for supporting improvement of this process and to raise its effectiveness for education of deaf children in Cuba. Keywords: visibility, impact evaluation, altmetrics, author identifier.